Konsep Eco Green Park pada Taman Bungkul Surabaya dalam Mewujudkan Environmental Sustainability - Rifdah Azizah Salsabila; Susy Budi Astuti (Universitas Sebelas Maret Surakarta, 2022)
Bungkul Park as one of the green open spaces in Surabaya is known as the best city park locally and internationally. The implementation and management of the park's environment has improved and developed over time. The aim of this paper was to determine whether Bungkul Park Surabaya has been effective in the ecological function of city parks and the application of SDGs to Bungkul Park facilities. The research method used in this study is qualitative by observing the activities of Bungkul Park visitors and conducting literature studies. The results of this paper indicate that Bungkul Park Surabaya needs to apply the concept of a green park to the waste system, structuring street vendors, and landscaping to support the Sustainable Development Goals.